1990
DOI: 10.1007/bf01310619
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of plants for virus resistance

Abstract: Historically, control of plant virus disease has involved numerous strategies which have often been combined to provide effective durable resistance in the field. In recent years, the dramatic advances obtained in plant molecular virology have enhanced our understanding of viral genome organizations and gene functions. Moreover, genetic engineering of plants for virus resistance has recently provided promising additional strategies for control of virus disease. At present, the most promising of these has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…Several strategies tested in annual plants, such as the expression of the viral coat protein, antisense RNA and interference with subviral RNA molecules (reviewed by Gadani et al, 1990 ;Szybalski, 1991) have been shown to be efficient in the control of virus diseases. Such strategies could be tested for virus protection in trees.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies tested in annual plants, such as the expression of the viral coat protein, antisense RNA and interference with subviral RNA molecules (reviewed by Gadani et al, 1990 ;Szybalski, 1991) have been shown to be efficient in the control of virus diseases. Such strategies could be tested for virus protection in trees.…”
Section: Introductionmentioning
confidence: 99%
“…Several successful attempts for engineering resistance to viral diseases in transgenic plants using viral-coat-protein (CP) coding sequences; expression of antisense viral transcripts and nucleic acid encoding viral satellite RNAs have been summarized (Gadani et al, 1990). Transgenic tobacco plants with full length cDNA copy of the genomic RNA of a mildly virulent tomato strain of tobacco mosaic virus (TMV-L11A) were more resistant to the highly virulent TMV-L strain than the CPmediated transgenic plants.…”
Section: Viral Diseasesmentioning
confidence: 99%
“…These findings open new avenues for plant protection in the most important agricultura1 crops. In most instances, CPMP extends only to the virus or to related strains with substantially similar coat protein, but there are a few instances where the expression of the viral coat protein of one virus can provide at least some limited protection of transgenic plants against heterologous virus infections ( Beachy et al, 1990;Gadani et al, 1990;Hull and Davies, 1992;Pang et al, 1992). In most cases, CPMP acts only against the virion, whereas inoculum consisting of naked virus RNA is frequently able to elicit infections.…”
Section: Cpmpmentioning
confidence: 99%
“…These molecules, which occur naturally in some virus systems, have the potential to be engineered to disrupt virus replication (for discussion and refs. see Gadani et al, 1990;Hull and Davies, 1992). Virus-mediated activation of toxic genes in transgenic host plants, over-expression of viral movement proteins, use of dominant negative mutants, and expression of combinatorial antibodies to specific virus proteins are strategies currently being explored in several laboratories for protection of plants from virus infections.…”
Section: Alternative Stratecies For Plant Protectionmentioning
confidence: 99%
See 1 more Smart Citation